Perlindungan Hukum Data Pribadi Debitur dalam Perjanjian Pinjaman Online (Fintech Lending) di Tinjau dari Hukum Perikatan di Indonesia - Dhiaul Azkiya; Fanisa Asyatilah Rusli; Fajar Caesar; Putri Zahra Mauliddina (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
The rapid growth of fintech lending in Indonesia has raised critical concerns over the protection of debtors' personal data, with frequent cases of data misuse, including unauthorized dissemination of contacts and coercive collection practices. This normative juridical research, employing statutory and conceptual approaches, examines the position of debtors' personal data within online loan agreements under Indonesian contract law, the available legal protections, and the liability of fintech lending providers for data breaches. The findings reveal that personal data serves a dual role in online loan contracts: as an object of processing and as a legally protected right, thereby influencing the validity of agreements under Article 1320 of the Indonesian Civil Code. Legal protection is primarily governed by Law No. 27 of 2022 on Personal Data Protection and OJK regulations, which guarantee debtors' rights to access, rectify, delete, and claim compensation. Fintech providers bear civil liability based on breach of contract and tort, and may also face administrative and criminal sanctions. This study implies that effective legal protection for debtors requires not only comprehensive regulations but also strengthened supervision, improved digital literacy, and the full establishment of personal data protection institutions to ensure accountability and redress in the fintech lending ecosystem.